Posttraumatic stress disorder in elite athletes - Lynch, J. H. (Current Sports Medicine Reports, 2021)
Posttraumatic stress disorder (PTSD), which may develop following exposure to severe trauma, can occur in all people at any age. PTSD affects approximately 10 million Americans, with an incidence of approximately 3.5% diagnosed every year. Elite athletes are not immune to posttraumatic stress. While difficult to precisely quantify, an estimated 1 in 8 elite athletes suffers from PTSD. Because of its complex presentation, PTSD can be challenging to diagnose and effectively treat in athletes. Several barriers unique to elite athletes exist which may inadvertently delay or prevent access to the appropriate clinical experts. Several best practice models for mental health screening in elite athletes have been developed in the past decade. Treatment of PTSD in the athlete population is similar to trauma-informed treatment in the general population, but should involve the athlete`s multidisciplinary team of clinical experts to account for unique demands and preferences in the context of sport.